Informed consent and research - Mandal, Jharna (Medknow Publications & Media Pvt Ltd, 2014)
Informed consent is the central doctrine to any research based on the principles of autonomy and self-determination. For it to be genuine and effective, it should be in simple regional language catering to the cultural and psychological and social requisites of the participant. The information entailed in the consent form must be true, should cover all the relevant aspects, and no fact should be hidden however seemingly important or unimportant. Every research volunteer puts his or her health and life at risk for the sake of science, and this must be respected at all times during the research.